2009
DOI: 10.1002/nbm.1432
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive detection of glycine as a biomarker of malignancy in childhood brain tumours using in-vivo 1 H MRS at 1.5 Tesla confirmed by ex-vivo high-resolution magic-angle spinning NMR

Abstract: Management of brain tumours in children would benefit from improved non-invasive diagnosis, characterisation and prognostic biomarkers. Metabolite profiles derived from in-vivo MRS have been shown to provide such information. Studies indicate that using optimum a priori information on metabolite contents in the construction of linear combination (LC) models of MR spectra leads to improved metabolite profile estimation. Glycine (Gly) is usually neglected in such models due to strong overlap with myo-inositol (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
53
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(62 citation statements)
references
References 32 publications
9
53
0
Order By: Relevance
“…It is likely that lactate detected in vivo in brain tumours is a measure of abnormal metabolic activity and not exclusively linked to tumour necrosis. The significant association between tumour grade and individual metabolites such as total choline, PCh, lipids and macromolecules, Gly, and Tau is also consistent with prior work, with elevated levels of these metabolites previously reported in high-grade brain tumours [14,37,45,47,70]. An association between increased NAA in low-grade glial tumours has also been previously identified [71].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…It is likely that lactate detected in vivo in brain tumours is a measure of abnormal metabolic activity and not exclusively linked to tumour necrosis. The significant association between tumour grade and individual metabolites such as total choline, PCh, lipids and macromolecules, Gly, and Tau is also consistent with prior work, with elevated levels of these metabolites previously reported in high-grade brain tumours [14,37,45,47,70]. An association between increased NAA in low-grade glial tumours has also been previously identified [71].…”
Section: Discussionsupporting
confidence: 78%
“…Tumour cells in astrocytic neoplasms stain intensely with antibodies to GFAP [36]; however, mIns in tumours has not yet been linked convincingly to this. Gly was detected in paediatric brain tumours in vivo by Davies et al [37] and it has been shown to be significantly higher in high-grade versus low-grade tumours. NAA is commonly regarded as a neuronal marker as it has been found to be preferentially highly expressed in neurons rather than glial cells [38].…”
Section: Introductionmentioning
confidence: 99%
“…ADP bound to F-actin in muscle microfilaments). In this respect, binding of gly to multimeric channel proteins in the plasma membrane of PC-12 cells (50) or to a glycine-sensitive anion death channel in sinusoidal endothelial cells (51) have been proposed. Increased gly content protects various types of cells from necrotic or apoptotic death induced by ATP depletion (PC-12 cells, (51)), hypoxia (hepatic sinusoidal cells, (52)) or ischaemia-reperfusion derived reoxygenation injury (cardiomyocytes, (53)).…”
Section: Comparison Of Mi/gly Calculated From In Vivo Data and Mi/glymentioning
confidence: 99%
“…Higher myoinositol levels in brain tumors may support the diagnosis of a low-grade astrocytoma , whereas higher glycine concentrations were found in high-grade gliomas as demonstrated in Fig. 6 Davies et al 2010).…”
Section: Tumor Grading and Heterogeneitymentioning
confidence: 88%